BREAKING STRENGTH AND STRETCHING (Elongation) PINEAPPLE LEAF STRAP MADE BY TWISTING TECHNIQUE BY SOAKING BAY LEAF EXTRACT (Syzygiumpolyanthum - Cindy Aldrina Anjella; Isnaniah Isnaniah; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRAKThe location for taking pineapple leaves is in Kualu Nenas Village, Tambang sub-district, Kampar district. which aims to determine whether there is an effect on the breaking strength and elongation of the pineapple leaf rope when soaked with bay leaf extract, using the experimental method, namely making the pineapple leaf rope by twisting it and testing its breaking strength. The results showed that the value of the breaking strength of the pineapple leaves before and after the bay leaf extract was soaked was 1.25 kgf and 2.02 kgf. For the value of the elongation of the pineapple leaf rope before and after soaking the bay leaf extract, they were 18 mm and 17.1 mm, respectively. Based on these results, it can be concluded that the breaking strength of the pineapple leaf rope soaked in bay leaf extract is higher than that of the pineapple leaf rope that is not soaked in bay leaf extract. However, for the elongation value of the pineapple leaf rope before soaking the bay leaf extract was higher.Keyword: Pineapple, breaking strength and elongation of the rope